FORMULASI SEDIAAN MASKER GEL DARI PATI JAGUNG MANIS (Zea mays saccharata) - Apriani, Aida; Nurfadhilah, Ika; Sirait, Tri Susanti; Azhari, Saiful; Samaniyah, Siti (UIN AR-RANIRY, 2024)
Corn is a popular ingredient in facial skin care products. Corn contains thiamine, which can dry wounds and eliminate acne scars that appear as holes on the face or black spots. Corn starch is made into a gel mask with the gelling ingredient hidroxy prophyl methyl cellulose (HPMC). This research intends to establish if a gel mask manufactured from sweet corn starch (Zea mays saccharata) can meet the requirements of the physical quality test assessment results, as well as the stability requirements. The research approach is experimental, employing a sample gathering methodology known as purposive sampling. The evaluation of gel mask preparations includes evaluating the physical quality of the preparations, irritant testing on 10 participants, and drying time tests on the preparations. The evaluation of the preparations revealed that all gel mask formulations were semi-solid gels with a yellowish white color and a distinct corny smell. The results were homogeneous, with an average pH of 7.5–7.7, spreadability of 5–7 cm, and viscosity of 22133-67566. The preparation also exhibited stable stability at room temperature and did not irritate volunteers' skin. Therefore, both the stability requirements and the physical quality test assessment results are satisfied by the preparation.